Spoken discourse - Jones, Rodney H. (New York Bloomsbury Academic, an imprint of Bloomsbury Publishing Plc, 2016)
"This book introduces a framework based on principles from mediated discourse analysis in which different approaches to spoken discourse are seen as complementing and informing one another. Spoken discourse is seen as mediated through a complex collection of technological, semiotic and cultural tools which enable and constrain people's ability to engage in different kinds of social actions, enact different kinds of social identities and form different kinds of social relationships. A major focus of the volume is on the way technological tools like telephones, broadcast media, digital technologies are changing the way people communicate with spoken language.--back cover.
What is spoken discourse? -- Studying spoken discourse -- Technologies of talk -- Talk in action -- Talk in interaction -- Talk and identity -- Talk and communities -- Answerability and the future of talk.
Includes bibliographical references (pages 199-213) and index.
Keywords: Discourse analysis -- Methodology; Conversation analysis; Sociolinguistics; Pragmatics